Analysis of the Use of E-Commerce among Students of UIN SMH Banten - Julfadli Fadillah; Fariz Syawal Putra; Ahmad Fajrillah; Wahyu Hidayat; Zaini Ibrahim (Jurnal Impresi Indonesia, 2024)
E-commerce has become an integral part of modern life, including among university students who increasingly rely on digital platforms to fulfill their daily needs. This study aims to understand the pattern of e-commerce use among students of UIN SMH Banten as well as the factors that influence their preferences in online shopping. This study uses a quantitative approach with a survey method. Data was collected through an online questionnaire distributed to 60 students from various faculties at UIN SMH Banten. The data obtained were analyzed using descriptive and inferential statistics to identify trends and correlations. The results showed that 85% of the respondents regularly use e-commerce to purchase various products, with fashion and electronic product categories being the most popular. Shopee and Tokopedia are the platforms most frequently used by college students. Key factors influencing purchasing decisions include ease of use of the platform, discount promotions, trust in transaction security, and product reviews from other users. Preferences for specific platforms and products are influenced by ease of access, price, and reputation for security. The findings indicate great potential for e-commerce providers to develop more effective marketing strategies tailored to students' preferences.